Functional Evaluation of Embedded Modular Single-Branched Stent Graft: Application to Type B Aortic Dissection With Aberrant Right Subclavian Artery - Zhang, Xuehuan; Chen, Duanduan; Wu, Mingwei; Dong, Huiwu; Wan, Zhengdong; Jia, Heyue; Liang, Shichao; Shao, Jun; Zheng, Jun; Xu, Shangdong; Xiong, Jiang; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Endovascular repair of type B aortic dissection (TBAD) with aberrant right subclavian artery (ARSA) is challenging due to anatomical complexity. The embedded modular single-branched stent graft (EMSBSG) could solve this problem. However, the hemodynamic efficacy of this innovative technique has not been fully assessed. This study aimed to propose morphometric and functional indicators to quantify the outcomes of EMSBSG in treating TBAD with ARSA. Material and Methods: A patient who had TBAD with ARSA underwent EMSBSG implantation was admitted. Computational fluid dynamics (CFD) and three-dimensional structural analyses were conducted based on CTA datasets before the operation (Pre-1) and at 4 and 25 days after EMSBSG implantation (Post-1 and Post-2). Quantitative and qualitative functional analyses were conducted via pressure-, velocity- and wall shear stress (WSS) -based parameters, such as the luminal pressure difference (LPD), total energy loss, and flow distribution ratio. By precisely registering the aortas at the three time points, parameter variations in the EMSBSG region were also computed to investigate the prognostic improvement after EMSBSG implantation. Results: The first balance point of LPD distally shifted to the abdominal aorta in Post-1 by a distance of 20.172 cm, and shifted out of the dissected region in Post-2, indicating positive pressure recovery post EMSBSG. The flow distribution ratios of all aortic arch branches increased after EMSBSG implantation. A positive normal deformation index in the EMSBSG region confirmed true lumen expansion; dominant ARN (area ratio of negative value) of pressure and WSS-based parameters indicated an improved prognosis from Post-1 to Post-2. Conclusions: The short-term results of EMSBSG in treating TBAD with ARSA proved to be promising, especially in EMSBSG region. Comprehensive evaluation could provide new insight into the therapy of TBAD with ARSA. Thus, it might guide the further management of complex aortic arch lesions.